Síndrome Frey en la consulta de alergología (2018)
ABSTRACT: Background: Frey’s syndrome is a group of symptoms that include unilateral sweating with malar region and external ear reddening after eating or drinking some food. It is a lesion of the auriculotemporal nerve that is secondary to surgery, parotid gland infection or facial trauma. Clinical cases: Three children between 4 and two and a half years of age: two girls and one boy. They had self-limiting unilateral erythematous facial macules that reached the external ear, withoutrash, itching, angioedema and gastrointestinal or respiratory symptoms; its onset was associated with the consumption of acid and some sweet foods. Symptom reproduction of was observed in the path of the auriculotemporal nerve. Their histories included cesarean section delivery owing to cephalopelvic disproportion (case 1), birth by operative vaginal delivery with forceps (case 2) and cesarean delivery owing to preeclampsia (case 3). Conclusions: Frey’s syndrome is often mistaken with food allergy, leading to unnecessary dietary restrictions.Sweating is often absent in children owing to possible eccrine glands immaturity.